Genome-Wide Analyses Reveal the Roles of CCT Genes as Regulators of Abiotic Stress Responses in Citrullus lanatus - Yajie Hong; Mengsha Li; Wona Ding; Jun Shi; Zishuo Zheng; Nailin Xing; Qiuping Li (Agronomy)
Members of the CCT gene family have been shown to play roles in photoperiodic flowering and environmental adaptation under a range of conditions. In this study, 29 CCT genes from watermelon were categorized into three distinct subfamilies. The ClCCT genes were systematically analyzed, focusing on their physicochemical properties, gene duplication, motifs, structural divergence, promoter regions, and collinearity with genes from other species. The responsiveness of these genes to abiotic stressors, hormone treatments, and photoperiod prolongation was also examined. Segmental duplication (gene amplification) significantly influenced the evolution of these genes, with most ClCCT genes containing light-, hormone-, and/or abiotic stimulus-responsive elements. In response to abiotic and hormonal stresses, 5 genes responded to cold, 1 gene to drought, and 4 genes to salt. 6 genes were responsive to ABA, and 13 genes to MeJA. Strikingly, ClCCT17, ClCCT4, and ClCCT28 responded to multiple stressors. A majority of these ClCCT genes and their homologs in other species were responsive to prolonged daylight exposure. The varying expression patterns of these genes suggested a key role for watermelon CCT genes in the regulation of both abiotic stress responses and flowering. Functional diversity was also evident among CCT family genes within a given species as well as among species attributable to changes in the structural features and expression patterns of the genes and the encoded proteins.